Public expenditure on agriculture, youth out-migration, and engagement in agriculture? Evidence from Nigeria - Amare, Mulubrhan; Takeshima, Hiroyuki; Abay, Kibrom A.; Omamo, Steven Were (International Food Policy Research Institute, 2025)
Theoretical models posit that migration decisions are driven by differences in economic opportunities across locations, including across rural and urban areas, which implies that increased rural investment can curb rural-urban migration and encourage engagement in agriculture. However, direct empirical evidence of this remains scant, especially on youth migration in Africa. We fill this knowledge gap by examining the effect of temporal changes in public expenditures for the agriculture sector (PEA) on rural youth’s migration and engagement in rural economies in Nigeria. We combine unique subnational data that capture PEA’s spatiotemporal variations and individual level youth data and estimate two-way fixed effects models. We find that a 1 percentage point increase (equivalent to a 25 percent increase) in the share of PEA, is associated with up to 0.9 percentage points reduction in youth’s out-migration. Conversely, an increase in PEA leads to increased youth engagement in farm activities. Our results suggest that public investments in rural economies can mitigate youth out-migration from rural areas. These results have important implications for informing youth and migration policies, especially in the context of Africa, often characterized by its youth bulge and the exodus of youth from rural areas because of perceived lack of economic opportunities.